Immunoinformatics and reverse vaccinology approach in designing a novel highly immunogenic multivalent peptide-based vaccine against the human monkeypox virus - Choudhury, Abhigyan; Chandra, Anshuman; Dawoud, Turki M.; Nafidi, Hiba-Allah; Singh, Nagendra; Bourhia, Mohammed (Frontiers in Molecular Biosciences, 2023)
Monkeypox is a highly infectious zoonotic disease, often resulting in complications ranging from respiratory illnesses to vision loss. The escalating global incidence of its cases demand prompt attention, as the absence of a proven post-exposure treatment underscores the criticality of developing an effective vaccine.Interactions of the viral proteins with TLR2 and TLR4 were investigated to assess their immunogenic potentials. Highly immunogenic proteins were selected and subjected to epitope mapping for identifying B-cell and MHC class I and II epitopes. Epitopes with high antigenicity were chosen, considering global population coverage. A multi-target, multi-epitope vaccine peptide was designed, incorporating a Beta defensin 2 adjuvant, B-cell epitopes, and MHC class I and II epitopes.The coordinate structure of the engineered vaccine was modeled and validated, on the other hand, its physicochemical properties, antigenicity, allergenicity, and virulence traits were evaluated. Molecular docking studies indicated strong interactions between the vaccine peptide and the TLR2 receptor. Furthermore, molecular dynamics simulations and immune simulation studies reflected its potent cytosolic stability as well as robust immune response dynamics induced by the vaccine.This study explored an innovative structure-guided approach in the use of immunoinformatics and reverse vaccinology in pursuit of a novel multi-epitope vaccine against the highly immunogenic monkeypox viral proteins. The simulation studies indicated the engineered vaccine candidate to be promising in providing prophylaxis to the monkeypox virus, nevertheless, further in vitro and in vivo investigations are required to prove its efficacy.